PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, DISIPLIN KERJA, DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR BADAN PENDAPATAN DAERAH (BAPENDA) LEBAK CABANG RANGKASBITUNG - Ipan Hilmawan (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
effect of transformational leadership style, work discipline, and spirit at work on employee performance (case study at BAPENDA Kab. Lebak branch office Rangkasbitung. This study aims to determine the effect transformational leadership style, work discipline, and morale of employee on employee performance. Technique of collecting data using questionnaire with likert scale measurement. All population in this research is were all populations in this study were sampled as many as 51 respondents using quantitative data analysis methods. The method used in this study is descriptive and Structural Equation Modeling (SEM) analysis techniques which are assisted by the SmartPLS 3.0 program. The results of this study are: (1) transformational leadership style has negative effect on employee performance with the results of > (5,151>2,011) .(2) work discipline had a positive affect on employee performance with the results of > (13,914>2,011). (3) spirit at work has positive affect and significant on employee performance. with the results of > (5,013>2,011).